A study on the effect of vessels delay and shut out of containers on MISC coastal liner service / Mohd Suhaimi Akbar Mohd Ramli - Mohd Ramli, Mohd Suhaimi Akbar (1994)
MISC (Malaysia International Shipping Corporation) has been regarded as one of the most successful Coastal Liner operators in the Coastal Trade. As the National Carrier, MISC cover many port of calls in East Malaysia namely Kuching, Sibu, Miri, Bintulu, Labuan, Muara (Brunai), Kota Kinabalu, Sandakan and Tawau.